2016
DOI: 10.1073/pnas.1516945113
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Solar photothermochemical alkane reverse combustion

Abstract: A one-step, gas-phase photothermocatalytic process for the synthesis of hydrocarbons, including liquid alkanes, aromatics, and oxygenates, with carbon numbers (Cn) up to C13, from CO2 and water is demonstrated in a flow photoreactor operating at elevated temperatures (180–200 °C) and pressures (1–6 bar) using a 5% cobalt on TiO2 catalyst and under UV irradiation. A parametric study of temperature, pressure, and partial pressure ratio revealed that temperatures in excess of 160 °C are needed to obtain the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Thep hotothermal effect can be described as the conversion of photon energy into heat and has been considered as an emerging technology of great interest for solar energy harvesting. [4] As this technology can enable aremarkable and prompt increase in the local temperature at the nanometer scale,i th as found ab road range of applications in various fields,i ncluding solar power generation, localized water heating, seawater desalination, and catalysis. [4a,b,5] It is well known that thermodynamically stable CO 2 molecules are more reactive at high temperatures.…”
mentioning
confidence: 99%
“…Thep hotothermal effect can be described as the conversion of photon energy into heat and has been considered as an emerging technology of great interest for solar energy harvesting. [4] As this technology can enable aremarkable and prompt increase in the local temperature at the nanometer scale,i th as found ab road range of applications in various fields,i ncluding solar power generation, localized water heating, seawater desalination, and catalysis. [4a,b,5] It is well known that thermodynamically stable CO 2 molecules are more reactive at high temperatures.…”
mentioning
confidence: 99%
“…directly combined Fe‐based or Cu/ZnO catalysts for thermocatalytic hydrogenation of CO 2 with photocatalytic water splitting . Recently, MacDonnell and co‐workers reported a one‐step, gas‐phase photothermocatalytic process for the synthesis of hydrocarbons from CO 2 –H 2 O in a flow photo reactor with a Co/TiO 2 catalyst under UV illumination . These preliminary and encouraging results show that the photothermocatalytic process is efficient in enhancing the conversion of CO 2 –H 2 O into fuels by using solar energy and is worthy of further extensive study.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid consumption of the generated hydrogen by direct thermocatalytic hydrogenation of CO 2 to produce alkanes greatly accelerates the migration of photogenerated electrons and thus lowers the recombination rate of photogenerated electrons and holes, providing a synergistic effect between photocatalysis and thermocatalysis in the direct thermophotocatalytic reduction of CO 2 –H 2 O. Recently, MacDonnell and co‐workers reported a similar photothermochemical process that used Co/TiO 2 for both photocatalytic water splitting and Fischer—Tropsch synthesis . They suggested that the products of photocatalysis could be consumed in thermal reactions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations